Metrology for Transient Reactor Characterization Using Uranium Wires. (3rd October 2019) - Holschuh, Thomas; Watson, Scott; Chichester, David
Abstract: The Transient Reactor Test (TREAT) facility, located at Idaho National Laboratory, restarted transient operations in 2018 following an extended shutdown. It is of interest to establish a methodology and capability to obtain an accurate estimate of the total number of fissions produced in a fissionable test item during a transient at TREAT. Uranium wires were irradiated in TREAT as part of a transient prescription test program, and gamma-ray spectrometry was performed on the wires following irradiation using a high-purity germanium detector. Many fission products are useful for estimating the number of fissions produced in a sample using gamma-ray spectrometry; at TREAT with the time periods used for analysis, the isotopes of interest include 95 Zr, 95 Nb, 103 Ru, 140 Ba, and 140 La. The number of fissions per gram of 235 U determined from these measurements establishes an estimate for future experiments to be performed in the core when a similar configuration is used with a similar transient prescription.